Pain Therapy. - Del Missier, Giovanni; Colautti, Laura (Medicina e Morale, 2002)
The article examines the elements of novelty brought by the Italian Act n. 12 of February 19, 2001 on the "Norms to facilitate the employment of opiate drugs in the pain therapy". Under the ethical point of view, the normative is positive according person-centered perspective to the extent that promotes a disinterested solidarity toward the patient. Besides, it is remembered that although the use of opiate drugs in some cases causes the anticipation of the death, this doesn't have to hinder their correct use: if there are no other possibilities of intervention, if the burden is proportionate to the risk and if the intention of who acts is determined by the only purpose to relieve the pain, without, in some way, to get the death. Similarly, the authors remember that the pain therapy is ethically acceptable even if it causes less clear-headedness up to the loss of conscience, but only after having given the patient the possibility to carry out his/her moral, family and religious duties and in the cases in which suffering is really serious, violent and unbearable.